Role of Cardiac Troponin I in Case of Death Time EstimationAn in Vitro Study - Boddupally Ravi Kumar1 , Prakash Chandra Jha2 , Shakti Shishodia3 , Dattatraya P. Kale4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background- Beta blockers are used for treating hypertension but few of them when taken in overdosecan be fatal. Acebutolol is one such beta-adrenoreceptor blocking agent that is considered one of the mosttoxic beta blockers when taking overdose. Determination of postmortem interval is a common practice inmedicolegal investigation.Objective: The present study was conducted to investigate the degradation pattern of cTnI with respect totime.Materials And Methods: Group 1 were anesthetized with Sodium pentobarbital (40 IP). The chest cavitywas then quickly opened, and the heart was excised out. Group 2 (Asphxial Death) were sacrificed byclamping a tracheostomy tube. Group 3 (Acebutolol Death) were sacrificed by giving an oral lethal dose ofAcebutolol(6620mg/kg). Incubation at 28º C for different time interval (0 hrs, 6 hrs, 12 hrs, 24hrs, 48 hrs,72 hrs, 96 hrs and 100 hrs). The heart was then isolated and freezed at-80ºC.The extraction of protein fromtissue was optimized so as to stop or minimize the degradation of protein during the extraction process. Theconventional method was used for extraction with slight modifications in the extraction buffer and an addedstep of carrying every step of the extraction process at low temperature (1-4ºC)Results- The data clearly established that the degradation pattern of cTnI is different for all the three groupsControl, Acebutolol and Asphyxia. In case of Acebutolol the degradation of cTnI into its molecular fragmentsis at a much faster rate when compared to the Control and Asphyxia groups, The difference in degradationof cTnI is because Acebutolol is highly cardiotoxic, and its effect on cardiac tissues is high and immediate.Conclusion- The degradation of intact cTnI into smaller molecular fragments is also dependent upontemperature. In order to know more about the measurement of cTnI fragmentation for the determination ofthe postmortem interval, further investigations are necessary to understand more about the cTnI degradationpattern.